A comparative study on the adherence to anti-hypertensive medications in urban and rural areas of Hubballi - Katapadi, Pratibha Rao; Bant, Dattatreya D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension is a significant public health issue worldwide and can have deleterious effects on the health when it is not under control. Adherence to antihypertensive medications is thus necessary for better control of blood pressure and to reduce the risk of complications. There are various factors which support or hinder the patient’s adherence to anti- hypertensive treatment. Thus this study was done to reflect the factors influencing the adherence to antihypertensive drugs among urban and rural population. Methods: A community based cross sectional study was conducted in urban and rural field practice areas of Karnataka Institute of Medical Sciences, Hubballi. A semi-structured questionnaire was used for data collection among the known hypertensive patients. The data was entered in Microsoft Excel and analysed using SPSS software. Results: Most of the hypertensive patients were aged 45 and above (89.5%). A total of 73.5% of the participants were adherent to antihypertensive medications and adherence was more among urban (76%) as compared to rural population (71%). Knowledge regarding complications of uncontrolled hypertension was the major factor for adherence in both the areas. The mean systolic and diastolic blood pressure was controlled in patients who were adherent. Conclusions: There is a higher level of adherence to antihypertensive medications in urban population as compared to rural population of Hubballi. The findings suggest patient factors, clinical factors and socio-demographic factors play an important role in determining the adherence to the medication.